2011
DOI: 10.1614/ipsm-d-10-00047.1
|View full text |Cite
|
Sign up to set email alerts
|

Restoring Native Plant Communities in Smooth Brome (Bromus inermis)–Dominated Grasslands

Abstract: Smooth brome (Bromus inermis) is an introduced, cool-season perennial, sod-forming grass that has been shown to invade both native cool-and warm-season grasslands throughout North America. During the fall of 2005 through spring 2007, we implemented a smooth brome removal study at five sites in eastern South Dakota. Sites were selected to represent a range of soil and environmental conditions. Seven fall herbicide treatments, five spring herbicide treatments, an untreated plot that was planted with a native see… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
9
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(12 citation statements)
references
References 34 publications
3
9
0
Order By: Relevance
“…However, the increased performance of nonnatives is usually associated with changes in resource availability or disturbance regimes (Daehler, ), which may explain why we found many studies that reported that the removal of nonnative species led to competitive release of other nonnatives. In a few instances, the percent increase in the nonnative species was equivalent to the release of neighboring native species (Alvarez & Cushman, ; Truscott et al ., ; Stephens et al ., ), but in most cases, the increase in nonnative cover significantly exceeded that of native species (Adler et al ., ; Brooks, ; Allen et al ., ; MacDougall & Turkington, ; Ogden & Rejmánek, ; Hulme & Bremner, ; Story et al ., ; Bush et al ., ; Cox & Allen, , ; Ortega & Pearson, ; Bahm et al ., ; Skaer et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…However, the increased performance of nonnatives is usually associated with changes in resource availability or disturbance regimes (Daehler, ), which may explain why we found many studies that reported that the removal of nonnative species led to competitive release of other nonnatives. In a few instances, the percent increase in the nonnative species was equivalent to the release of neighboring native species (Alvarez & Cushman, ; Truscott et al ., ; Stephens et al ., ), but in most cases, the increase in nonnative cover significantly exceeded that of native species (Adler et al ., ; Brooks, ; Allen et al ., ; MacDougall & Turkington, ; Ogden & Rejmánek, ; Hulme & Bremner, ; Story et al ., ; Bush et al ., ; Cox & Allen, , ; Ortega & Pearson, ; Bahm et al ., ; Skaer et al ., ).…”
Section: Discussionmentioning
confidence: 98%
“…Grassland restoration often solely focuses on broad objectives such as a reduction of invasive species cover (e.g. Bahm et al ) or recuperation of community composition (e.g. Case et al ).…”
Section: Discussionmentioning
confidence: 99%
“…The ideal timing and concentration of application differ between chemicals and target species (e.g. Bahm et al ), and the choice of chemical and application rate can also impact the non‐target effects to flora and fauna in the community (Olszyk et al ). In many cases, vertebrates, including birds, mammals, and reptiles, are not affected greatly by herbicides (Lindenmayer et al ).…”
Section: Discussionmentioning
confidence: 99%
“…Smooth brome invasion into intact native grasslands has been extensively studied [9][10][11][12][13][14][15][16][17] . Smooth brome invasion radically changes plant community structure 15,16 , and subsequently causes changes in soil nutrient cycling and soil microbial community structure and function [9][10][11]18,19 .…”
Section: Background and Summarymentioning
confidence: 99%